2012
DOI: 10.1186/2045-9912-2-21
|View full text |Cite
|
Sign up to set email alerts
|

A basic study on molecular hydrogen (H2) inhalation in acute cerebral ischemia patients for safety check with physiological parameters and measurement of blood H2 level

Abstract: BackgroundIn animal experiments, use of molecular hydrogen ( H2) has been regarded as quite safe and effective, showing benefits in multiple pathological conditions such as ischemia-reperfusion injury of the brain, heart, kidney and transplanted tissues, traumatic and surgical injury of the brain and spinal cord, inflammation of intestine and lung , degenerative striatonigral tissue and also in many other situations. However, since cerebral ischemia patients are in old age group, the safety information needs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 21 publications
5
63
0
3
Order By: Relevance
“…The solubility of hydrogen in blood is less than water and decreases with increasing temperature. Furthermore, difficulty in achieving consistent and adequate blood concentrations when hydrogen has been administered as gas has been previously reported in human subjects (22). This is one possible explanation for the negative finding in this present study.…”
Section: Discussionsupporting
confidence: 54%
“…The solubility of hydrogen in blood is less than water and decreases with increasing temperature. Furthermore, difficulty in achieving consistent and adequate blood concentrations when hydrogen has been administered as gas has been previously reported in human subjects (22). This is one possible explanation for the negative finding in this present study.…”
Section: Discussionsupporting
confidence: 54%
“…Studies using other rat models confirmed the effects of hydrogen on the improvement of neurological function (Cai et al , 2008; Chen et al , 2010; Matchett et al , 2009). A recent clinical study treated 13 cerebral ischemia patients with hydrogen inhalation and showed that 3–4% hydrogen inhalation over 30 mins was feasible and safe in stroke patients (Ono et al , 2012). …”
Section: Medical Gasesmentioning
confidence: 99%
“…Because hydrogen gas has no foreign smell, it can easily be inhaled into the body [21]. Although some reports have shown that complications involving facemasks and unattended patients, specifically neurologically impaired patients, may cause inconsistencies with inhalation.…”
Section: Mechanismsmentioning
confidence: 99%